Empirical analysis of the “shimer puzzle” - Fumitaka Furuoka; Beatrice Lim; Khairul Hanim Pazim; Li Jingyi (Universiti Malaysia Sabah, 2020)
This paper aims to examine the “Shimer Puzzle” by using a dynamic stochastic general equilibrium (DSGE) approach. The appropriate calibrate strategy could assist in solving two aspects of the Shimer puzzle by generating more accurate standard errors for unemployment and elasticity of the v–u ratio with respect to productivity. However, there remains the unsolvable problem of generating an accurate standard deviation for vacancy.